Language as a Tool for Multinational companies, Insights on the Issue, including Albanian Market Proposal for Research - Çiço, Olda; Dishmema, Elfrida; Kadiu, Edmond (European Journal of Sustainable Development, 2014)
We communicate with words. Language as a tool of understanding, giving responses, making decisions, and having a better way to reach business goals is to be under consideration. This paper aims to explain why globalization has a very important impact on management, particularly because of the language used during various work aspects of multinational companies. The focus is why experience in this kind of research suggests writing on this issue and trying to implement the past results in Albania. While Albania is facing the integration process and it is part of a globalized economy, it has to be considered the fact that we are expecting more foreign investments, even from multinational companies. Cross-cultural problems are to be taken under consideration, especially the language. Keywords: Language, knowledge, Diversity, Multinational Companies, Albania, Performance.